Online Reading Strategies in EFL: A Review - Parlindungan Pardede (Journal of English Teaching, 2022)
Online reading strategies have been a crucial issue in EFL learning because reading strategies are essential for students reading comprehension and the increasing penetration of information and communication technology into foreign language learning has transformed reading and current studies have shown that online text reading requires new strategies. This article presented the findings of a systematic review of 20 research on online reading strategies in EFL learning published in 2011-2021. The findings of the studies focusing on the strategy used for EFL online reading show that the most frequently used reading strategies were problem-solving strategies, which is followed by global reading strategies, and finally support strategies as the least frequently used strategies. The findings concerning the correlation of online reading strategies and other variables of reading are inconclusive because each of the studies correlates online reading with different reading variables. Results of studies focusing on the effectiveness of online reading strategies are also inconclusive because each of them investigated the effect of online reading strategies on different variables. Thus, more and more studies are needed to provide a clearer understanding of online reading strategies.